Management of Educational Administration of Semarang Police Academy - Salafudin , Moh. Anwar (2012)
This study aims to describe the characteristics of educational administration of leadership, public devotion, and Spirituality in Semarang Police Academy. This study is a qualitative study using an ethnographic design. The research was conducted in Semarang Police Academy. Informants in this study is the faculty, staff, cadets and midshipmen Of Semarang police academy caregivers. Methods of collecting data using interviews, observation, and documentation. The results showed: (1) Semarang police academy has 3 patterns of education, namely teaching, training and parenting, in management of educational administration of leadership were also conducted with three patterns. The process of learning taught courses in leadership in general can be done in the classroom and also outside the classroom, teaching in the classroom before starting daily as class president Commander platoon daily report to the teacher cadets ready for lessons. Educational leadership of Semarang police academy using peer tutors. Educational leadership by selecting cadets corps officer, who was chosen because of the potential and ranking. Officer cadets are given rewards, but if you violate sanctioned 2 times more than the usual cadet, there also remains the official addition to the daily official, Commander platoon either daily or daily class president. Caregiver parenting accompanied by cadets, as well as the appointment of younger foster brother and foster care by senior cadets and juniors, (2) In exercising dedication to the community undertaken periodically and incidental, Dedication to the community, periodically through social studies and Training Midshipman at the end of the semester, Dedication to the community, incidental implemented if there is a natural disaster or event that requires assistance to communities, (3) The learning process in Of Semarang police academy includes 3 aspects of physical, mental and spiritual. Includes two teaching spiritual formation, in the classroom and outside the classroom with courses that can be grouped in spirituality, and spiritual guidance Friday and Sunday, and every afternoon, and practiced in daily life. spiritual learning in the classroom, in addition to using the method of discussion is usually also done using the method of question and answer or lecture. Every Friday and Sunday brings the chaplain or preacher to give the youth a spray spiritual